2018
DOI: 10.1021/acsnano.8b03865
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Expansion and Fate Decision on Liquid Substrates Are Regulated by Self-Assembled Nanosheets

Abstract: The culture of adherent cells is overwhelmingly relying on the use of solid substrates to support cell adhesion. Indeed, it is typically thought that relatively strong bulk mechanical properties (bulk moduli in the range of kPa to GPa) are essential to promote cell adhesion and, in turn, regulate cell expansion and fate decision. In this report, we show that adherent stem cells such as mesenchymal stem cells and primary keratinocytes can be cultured at the surface of liquid substrates and that this phenomenon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 48 publications
8
79
0
Order By: Relevance
“…In contrast, HPKs on soft nanosheets present a lower degree of cell spreading, decreased FAs and disorganised actin fibres. Reproduced with permission from Kong et al (2018b) where it was published under a Creative Commons Attribution license (CC BY 4.0).…”
Section: Softmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, HPKs on soft nanosheets present a lower degree of cell spreading, decreased FAs and disorganised actin fibres. Reproduced with permission from Kong et al (2018b) where it was published under a Creative Commons Attribution license (CC BY 4.0).…”
Section: Softmentioning
confidence: 99%
“…oil). These nanosheets can be assembled from bovine serum albumin (BSA) (Kong et al, 2018a) or poly-L-lysine (PLL) (Kong et al, 2018b), and their interfacial shear stress moduli can be tuned by modifying the concentration of pro-surfactant and the pH during self-assembly, respectively. Moreover, PLL polymer nanosheets can be coated with fibronectin, which enables the adhesion and culture of adherent stem cells, such as MSCs and human primary keratinocytes (HPKs) (Fig.…”
Section: Nanoscale Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…With addition of reactive surfactant pentafluorobenzoyl chloride, the mechanics of protein layer is enhanced, which can promote cell adhesion and proliferation. The same research team reported expansion and fate decision of stem cells with self‐assembled nanosheets . The used polymer nanosheets was made from cationic poly(L‐lysine) and reactive surfactant pentafluorobenzoyl chloride, to which extracellular matrix protein can be adsorbed.…”
Section: Nanoarchitectonics For Cell: Physical Mechanical Factorsmentioning
confidence: 99%
“…The same research team reported expansion and fate decision of stem cells with self-assembled nanosheets. [29] The used polymer nanosheets was made from cationic poly(L-lysine) and reactive surfactant pentafluorobenzoyl chloride, to which extracellular matrix protein can be adsorbed. With strong mechanical properties, cell spreading and proliferation can be controlled.…”
Section: Cells At Liquid Interfacementioning
confidence: 99%